Uwarunkowania działalności małych i średnich przedsiębiorstw (MSP) w sektorze ochrony zdrowia na przykładzie firmy medycznej PROMED - Fryczewska, Marta (My University, 2012)
Praca magisterska napisana z zakresu przedsiębiorczości i zarządzania na temat uwarunkowań działalności małych i średnich przedsiębiorstw (MSP) w sektorze ochrony zdrowia na przykładzie „PROMED” S.C. Część badawcza poświęcona jest analizie podmiotu medycznego „PROMED” S.C. z sektora MSP. Przedstawiono szczegółową charakterystykę podmiotu badania (począwszy od genezy powstania firmy, poprzez zmiany zachodzące w związku z reformą zdrowia). Hipotezy testowane przy pomocy modelu Churchilla i Lewis’a wraz z jednoczesnym wskazaniem etapu rozwoju, w jakim się obecnie znajduje. Dokonano również diagnozy potencjału rozwojowego badanego podmiotu opierając się o analizę Przedsiębiorca - Organizacja – Strategia, jak również analizy SWOT oraz przedstawiono pozytywne i negatywne zjawiska. Analiza POS i analiza SWOT spełniła zakładany cel pracy wykazując, że małe i średnie przedsiębiorstwa można z powodzeniem analizować wymienionymi metodami i na podstawie otrzymanych wyników podjąć konkretne działania w wykrytych zjawiskach pozytywnych i negatywnych.

Master’s thesis was based on the issues relating to the entrepreneurship and the management. The leading theme is connected with conditionings concerning an activity of small and medium – sized enterprises in the health care sector on the example “PROMED” c.p. (ciwil law partnership) The research part is devoted to analysis of the medical entity "PROMED" c.p. as the subject from the small and medium-sized enterprises. In the thesis was presented a detailed characterization of the examined subject (starting from the genesis of the formation of the company, through changes happening in relation to the reform of the health). Hypothesis were tested by using model of Churchill and Lewis. Simultaneously there was indicated a stage of the development of the enterprise at present time. There were made also the diagnosis of the developmental potential of the studied subject based on analysis Entrepreneur - Organization – Strategy (EOS), SWOT analysis and there were presented positive and negative phenomena. EOS analysis and the SWOT analysis served an established purpose of the work showing that it is possible successfully to analyse small and medium-sized enterprises with exchanged methods and based on received results to take concrete actions in uncovered positive and negative occurrences.
Determinants of small and medium enterprises (SMEs) in the health sector on the example of the medical company PROMED
Keywords: MSP; PROMED S.C.; służba zdrowia; analiza POS; analiza SWOT; small and medium-sized enterprises; health service; model of Churchill and Lewis; EOS analysis; SWOT analysis; model Churchilla i Lewis